2016
DOI: 10.5539/res.v8n1p145
|View full text |Cite
|
Sign up to set email alerts
|

Deaths by Suicide in Ecuador: A Quantitative Data Analysis

Abstract: The aim of the present study was to investigate the profile of Ecuadorians who died by suicide during 2011. The National Mortality Study of 2011 was used in order to investigate the variables: sex, age, marital status, area of residence, natural region, level of instruction, ethnic self-identification, pregnancy and types of suicide. A descriptive analysis, a multiple correspondence analysis and a hierarchical classification were realized. The analysis showed that the majority of the Ecuadorians who died by su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 7 publications
1
5
0
Order By: Relevance
“…It also seeks to describe the concordance with the national reports related to this topic and describes the relationship between the variables under analysis and their characteristics by gender to conclude about it. In the framework of this study, a descriptive analysis was realized, and also a chi-square test that confirmed the results of the descriptive analysis (Sarmiento et al, 2016).…”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…It also seeks to describe the concordance with the national reports related to this topic and describes the relationship between the variables under analysis and their characteristics by gender to conclude about it. In the framework of this study, a descriptive analysis was realized, and also a chi-square test that confirmed the results of the descriptive analysis (Sarmiento et al, 2016).…”
Section: Resultssupporting
confidence: 55%
“…Despite the great advances in social development in Ecuador, a gap still exist according to the ethnic self-identification for example, the indigenous community shows lower percentages of development in education, mortality rate, satisfaction with the employment activity status, and so on (Castellano et al, 2017) Also, there is a relationship between the level of instruction and suicide. (Sarmiento et al, 2016) Based on what has been referenced, by means of a qualitative analysis of the data compiled by the ENEMDU 2015 survey (INEC, 2015); a national employment, unemployment and underemployment survey carried out by the Ecuadorian Institute of Statistics and Censuses (INEC), several important aspects are intended to be determined. Those are the demographic, economic, educational and social profile of men and women between 15 and 64 years of age in order to observe the existing characteristics and differences between these two groups to relate them to the development objectives planned by the state.…”
Section: Maternitymentioning
confidence: 99%
“…2.88% of the respondents have no education and 6.76% have University studies (Sarmiento et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Data about suicide is still scarce in Latin America, especially in smaller countries like Ecuador. In the last 20 years just very few reports have partially described this phenomenon in the country [ 24 26 ].…”
Section: Introductionmentioning
confidence: 99%